Life-Span Changes of the Human Brain White Matter: Diffusion Tensor Imaging (DTI) and Volumetry - Westlye, Lars T.; Walhovd, Kristine B.; Dale, Anders M.; Bjørnerud, Atle; Due-Tønnessen, Paulina; Engvig, Andreas; Grydeland, Håkon; Tamnes, Christian K.; Østby, Ylva; Fjell, Anders M. (Cerebral cortex (New York, N.Y. 1991), 2010)
Magnetic resonance imaging volumetry studies report inverted U-patterns with increasing white-matter (WM) volume into middle age suggesting protracted WM maturation compared with the cortical gray matter. Diffusion tensor imaging (DTI) is sensitive to degree and direction of water permeability in biological tissues, providing in vivo indices of WM microstructure. The aim of this cross-sectional study was to delineate age trajectories of WM volume and DTI indices in 430 healthy subjects ranging 8–85 years of age. We used automated regional brain volume segmentation and tract-based statistics of fractional anisotropy, mean, and radial diffusivity as markers of WM integrity. Nonparametric regressions were used to fit the age trajectories and to estimate the timing of maximum development and deterioration in aging. Although the volumetric data supported protracted growth into the sixth decade, DTI indices plateaued early in the fourth decade across all tested regions and then declined slowly into late adulthood followed by an accelerating decrease in senescence. Tractwise and voxel-based analyses yielded regional differences in development and aging but did not provide ample evidence in support of a simple last-in-first-out hypothesis of life-span changes.